2021
DOI: 10.3390/su132212792
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Interest Formation in English Learning through XploreRAFE+: A Gamified AR Mobile App

Abstract: The use of gamification and AR technology is found to have the capacity to enhance students’ interest. In this study, the researchers chose a class in a vocational college in China as a specific case that used the gamified AR mobile application, called XploreRAFE+. This study aimed to explore the use of XploreRAFE+ in the formation of learners’ interest in order to answer the research question: What is the process of interest formation among vocational college students in a gamified AR environment, and how doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
5
0
2
Order By: Relevance
“…As shown in Supplementary Table 1 , although there were some drawbacks of using gamification, many empirical studies reviewed reported that both students and teachers held a positive attitude toward using gamification in EFL/ESL learning and teaching, because a gamified course system did increase students’ motivation to learn ( Liu and Chu, 2010 ; Hwang et al, 2017 ; Ge, 2018 ; Homer et al, 2018 ; Hung, 2018 ; Sun and Hsieh, 2018 ; Ho, 2020 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Almusharraf, 2021 ; Chen, 2021 ; Kaban and Karadeniz, 2021 ; Qiao et al, 2022 ), stimulate students’ interest and engagement in learning English ( Hung, 2018 ; Kingsley and Grabner-Hagen, 2018 ; Sun and Hsieh, 2018 ; Ho, 2020 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Wang et al, 2021 ), help to create an authentic language environment ( Wu et al, 2014 ; Mei and Yang, 2019 ), help students to make improvements in English skills performance and competence ( Sandberg et al, 2014 ; Hung, 2017 ; Hwang et al, 2017 ; Sevilla Pavón and Haba Osca, 2017 ; Lam et al, 2018 ; Hashim et al, 2019 ; Hong et al, 2020 ; Zou, 2020 ), foster the habit of self-learning and realize learning autonomy ( Sandberg et al, 2014 ; Rueckert et al, 2020 ), and help students to get better knowledge retention ( Ge, 2018 ; Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Supplementary Table 1 , although there were some drawbacks of using gamification, many empirical studies reviewed reported that both students and teachers held a positive attitude toward using gamification in EFL/ESL learning and teaching, because a gamified course system did increase students’ motivation to learn ( Liu and Chu, 2010 ; Hwang et al, 2017 ; Ge, 2018 ; Homer et al, 2018 ; Hung, 2018 ; Sun and Hsieh, 2018 ; Ho, 2020 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Almusharraf, 2021 ; Chen, 2021 ; Kaban and Karadeniz, 2021 ; Qiao et al, 2022 ), stimulate students’ interest and engagement in learning English ( Hung, 2018 ; Kingsley and Grabner-Hagen, 2018 ; Sun and Hsieh, 2018 ; Ho, 2020 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Wang et al, 2021 ), help to create an authentic language environment ( Wu et al, 2014 ; Mei and Yang, 2019 ), help students to make improvements in English skills performance and competence ( Sandberg et al, 2014 ; Hung, 2017 ; Hwang et al, 2017 ; Sevilla Pavón and Haba Osca, 2017 ; Lam et al, 2018 ; Hashim et al, 2019 ; Hong et al, 2020 ; Zou, 2020 ), foster the habit of self-learning and realize learning autonomy ( Sandberg et al, 2014 ; Rueckert et al, 2020 ), and help students to get better knowledge retention ( Ge, 2018 ; Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al ( 2021 ) found that introducing new technology, gamification, and AR technology as a mobile APP, acted as a drive to awaken students’ curiosity. This caused to attract students and stimulates their interest.…”
Section: Discussionmentioning
confidence: 99%
“…Otro punto importante es que se identifica que la mayoría de los estudios implementan la ludificación por periodos cortos de tiempo, por ejemplo, en actividades hechas en Kahoot y Quizzes. Aún así, se puede revisar que Philpott (2020) y Wang et al, (2021) ludificaron sus cursos por periodos prolongados de tiempo. Estos autores tienen en común que indicaron haber basado sus intervenciones en teorías de ludificación y de motivación, como lo es la teoría de la autodeterminación.…”
Section: Antecedentesunclassified